Impact of irradiation on metabolomics profile of ground meat and its implications toward food safety. (1st May 2022) - Panseri, Sara; Arioli, Francesco; Pavlovic, Radmila; Di Cesare, Federica; Nobile, Maria; Mosconi, Giacomo; Villa, Roberto; Chiesa, Luca Maria; Bonerba, Elisabetta
Abstract: Irradiation is a reputed efficient sterilizing method that demonstrated valuable effects on meat preservation. This research, based on qualitative untargeted HPLC-Orbitrap metabolomics approach, was intended to estimate the variations in global metabolome profile of irradiated chicken, turkey, and mixed (chicken, turkey, and pork) ground meat to assess the possible presence of a food safety issue concerning the metabolome alteration. Overall, 402 metabolites were identified, and all three matrices exhibited a specific metabolome profile that was not influenced remarkably by the application of five different levels of irradiation intensity. In particular, all three meat categories displayed the following common features: 1) free amino acids pool remained unaffected by irradiation 2) taurine appeared as the most important differentiator for all three category 3) amount of glutathione decreased 4) characteristic although minor, oxidative modifications of polyunsaturated free fatty acids occurred 5) intensified adenosine nucleotide degradation. The presented analytical approach highlighted the usefulness of meat metabolome profiling in distinction of irradiated meat from non-treated one. Metabolomics analysis did not diagnose any relevant negative impact of irradiation on meat safety issues, but contemporary has demonstrated alternations in few metabolic pathways. Highlights: HPLC-HRMS-Q-Orbitrap was used for metabolome profiling of irradiated meat. Metabolomics is useful in distinguishing between irradiated and nonirradiated food. The most important differentiators are involved in PUFA oxidation pathway. Irradiation altered the AMP metabolism. Metabolome profiling revealed no negative impact of irradiation on meat safety.